Upregulation of Apoptotic Protein and Migration-Inhibitory Effects of Gallic Acid and Methyl Gallate Combined with Cisplatin in HeLa Cervical Cancer Cells - Hasmah Abdullah; Norlida Mamat; Syahirah Sazeli; Hermizi Hapidin; Sarina Sulong; Illyana Ismail; Deena Elsori (Tropical Life Sciences Research, 2026)
The study investigated the effects of gallic acid (GA) and methyl gallate (MG), in combination with cisplatin (CIS), on apoptotic protein expression, antioxidant gene expression and cell migration in HeLa cervical cancer cells. HeLa cells were treated with the combinations CIS–GA and CIS–MG prior to further analysis. The expression of apoptotic proteins (Bax, Bcl-2, caspase-3, caspase-9 and p53) was determined via western blot analysis. Antioxidant gene expression in treated HeLa cells was then assessed using reverse transcription quantitative polymerase chain reaction (RT-qPCR). The migration-inhibitory effect of the compound combinations was assessed using a scratch wound-healing assay. Treatment with CIS–GA significantly upregulated the expression of p53, Bax, caspase-3 and caspase-9, and downregulated the expression of Bcl-2. Results from RT-qPCR revealed downregulation of human catalase (hCAT) in the CIS–GA group and no changes in superoxide dismutase 1 (SOD1) expression in either the CIS–GA or CIS–MG groups. Moreover, lower wound closure percentages were observed after 24-hour incubation in both treated groups, indicating inhibited cell migration. These findings suggest that GA and MG combined with CIS upregulate apoptotic proteins by downregulating antioxidant gene (hCAT).